Modular Steel Buildings Based on Self-Locking-Unlockable Connections Seismic Performance Analysis - Xingwang Liu; Qingkai Meng; Liwen Xu; Yang Liu; Xinpeng Tian (Buildings)
This paper introduces a new self-locking-unlockable modular building with an inter-module connection, and its seismic performance is investigated. The new connection can realize fast connection and unlocking during construction through exceptional design. In this paper, taking the Tianjin Binhai Apartment project as the background, for the actual force situation of the new connection, considering the influence of corrugated steel plate stiffness, a simplified model of the connection is constructed by using multi-fold elastic connection, and the corrugated steel plate stiffness is simulated with equivalent support. In the MIDAS Gen 2021 software, the five-story and six-story structural models using traditional rigid connections and new connections were established, respectively, and reaction spectrum analysis was carried out. Meanwhile, seismic waves that comply with codes were selected for dynamic time course analysis. The results show that the stress ratios of all components of the new connection model and the traditional rigid model are less than 1. Among them, the maximum stress ratios of both floor beams are 0.745 and 0.725, respectively; the maximum stress ratios of the modular columns are 0.655 and 0.494, respectively; the stress ratios of the ceiling beams are all less than 0.5; and the two models show good strength and stiffness reserves, following the design principle of strong columns and weak beams and verifying the reliability of the new connection model. Meanwhile, it is found that the inter-story displacement angle of the six-story structure with the new connections is less than the normative value under the action of rare earthquakes, and the difference in top displacement is about 18% compared with that of the rigid structure, so it is suggested that the new connections can be applied within the height of six stories.